1995
DOI: 10.1007/s002800050341
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topoisomerase I inhibitors, topotecan and irinotecan, administered at low dose levels in protracted schedules to mice bearing xenografts of human tumors

Abstract: The efficacy of protracted schedules of therapy of the topoisomerase I inhibitors 9-dimethyl-aminomethyl-10-hydroxycamptothecin (topotecan) and 7-ethyl-10-[4-(1-piperidino)-1-piperidino]-carbonyloxycamptothecin (irinotecan; CPT-11) were evaluated against a panel of 21 human tumor xenografts derived from adult and pediatric malignancies. Tumors included eight colon adenocarcinomas, representing an intrinsically chemorefractory malignancy, six lines derived from childhood rhabdomyosarcoma (three embryonal, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 0 publications
5
141
1
Order By: Relevance
“…Similarly, CPT-11 was administered only as a single LD 0 bolus. Higher response rates and increased tumour growth inhibition have been reported with fractionated regimens in mice, for example, every 4 days for 3 cycles (Lavelle et al, 1996), 6-day courses (O'Leary et al, 1999), or at low doses (10 mg kg À1 ) in protracted schedules of several weeks (Houghton et al, 1995), administering a higher total dose. Regardless, CPT-11 retards tumour growth with or without anti-VEGF mAb pretreatment, and our data certainly do not show antagonism between CPT-11 and anti-VEGF mAb.…”
Section: Tumour Growth Delaymentioning
confidence: 97%
“…Similarly, CPT-11 was administered only as a single LD 0 bolus. Higher response rates and increased tumour growth inhibition have been reported with fractionated regimens in mice, for example, every 4 days for 3 cycles (Lavelle et al, 1996), 6-day courses (O'Leary et al, 1999), or at low doses (10 mg kg À1 ) in protracted schedules of several weeks (Houghton et al, 1995), administering a higher total dose. Regardless, CPT-11 retards tumour growth with or without anti-VEGF mAb pretreatment, and our data certainly do not show antagonism between CPT-11 and anti-VEGF mAb.…”
Section: Tumour Growth Delaymentioning
confidence: 97%
“…Additional studies with prolonged exposure schedules in mice bearing xenografts of colon adenocarcinoma, rhabdomyosarcoma and brain tumours showed less toxicity and better anti-tumour activity than dose-intensive short-exposure schedules (Houghton et al, 1995). These in vivo studies show that oral administration is as efficacious as parental application, although the AUC is lower with oral administration.…”
Section: Preclinical Studies In Vitro Studiesmentioning
confidence: 78%
“…TPT administration resulted in responses of xenografts not responsive to a short-term parental intermittent high-dose schedule (Houghton et al, 1991(Houghton et al, , 1995.…”
Section: Preclinical Studies In Vitro Studiesmentioning
confidence: 99%
“…Preclinical data have indicated that topoisomerase I inhibitors, like topoisomerase II inhibitors, demonstrate more efficacy with prolonged continuous exposure (Houghton et al, 1995).…”
Section: Discussionmentioning
confidence: 99%